From chatbots to conversational commerce: The role of AI in shaping consumer purchase decisions - Muliansyah, Dadah; Nurhidayah, Rika (RIGGS: Journal of Artificial Intelligence and Digital Business, 2024)
As conversational artificial intelligence (AI) continues to transform digital commerce, understanding how chatbot-mediated interactions shape consumer decision-making is essential. This study investigates the role of AI-based chatbots in influencing consumer purchase behavior through real-time, natural language communication. Focusing on the emerging dimensions of perceived empathy and trust, the research employs a mixed-methods approach combining a quantitative survey (n = 420) and qualitative text mining of chatbot dialogues collected from the used car sales sector in the Tangerang region, Indonesia. Findings reveal four key insights: (1) perceived empathy strongly predicts consumer trust, (2) trust in AI significantly drives behavioral intention to purchase, (3) empathy also directly influences intention, and (4) empathetic language triggers engagement during chatbot interactions. These results demonstrate that affective communication by AI agents is a critical driver of consumer responses in digital transactions. The study extends the Technology Acceptance Model by integrating emotional constructs and contributes to human resource and marketing strategy by showing how emotional intelligence, when encoded into AI systems, affects relational and behavioral outcomes. Despite the geographic and sectoral limitations of the sample, the findings underscore the growing need to humanize AI communication in commerce. Future research should explore cross-cultural validations and assess AI–human interaction in broader organizational contexts.